Synthesis of Novel 2,4-Disubstituted Bioactive Thiazoles - Ghani*, Ambreen; A. Hussain, Erum; Yasmeen, Abida; Naz, Narjis; Asghar, Shaheen (Asian Journal of Chemistry, 2014)
A series of 2,4-disubstituted thiazoles was synthesized by iodine mediated method in good to excellent yield. All the novel compounds were evaluated for in vitro anti-mutagenic activity, revealing synergistic results. The structures of all new fabricated compounds were characterized by FTIR, UV and MS techniques.